Effect of Fermentation with The Addition of Yeast Tape on The Sensory Quality of Gayo Arabica Coffee. Issue 1 (1st December 2022) - Assayuti, M; Fadhil, R; Erika, C
Abstract: This research has a purpose to evaluate the impact of fermentation with the addition of tape yeast affected the sensory quality of Gayo arabica coffee. The coffee processing process is accomplished naturally anaerobically with a dose of yeast addition tape of 0, 10, 30, and 60 grams. The attributes evaluated by the certified panelists were acidity, aftertaste, fragrance, flavor, body, sweetness, uniformity, clean cup, balance, defect, and overalls. The results revealed that fermentation with yeast additions of 0 grams and 10 grams did not significantly impact the sensory arabica coffee Gayo's quality. The addition of 30 grams and 60 grams of yeast tape shows a noticeable difference in the resulting sensory quality.